Money Demand Stability with Endogenous Structural Breaks and the Role of Payment System Innovation in Indonesia - Wishnu Badrawani (Universitas Negeri Malang, 2025)
This study examines the stability of the demand for money function in Indonesia using quarterly data from 2007 to 2021, employing Gregory-Hansen's (1996) cointegration test and Hendry's general-to-specific approaches. The cointegration and error correction models show a causal relationship between money demand and its conventional determinants and payment system innovation. Considering the central bank policy that part of economic reforms captured by the structural break in the cointegration test and the stability test results of the short-run analysis, we confirm the stable narrow money and currency demand and its dynamics in Indonesia. The Gregory and Hansen test found a cointegrating relationship between money demand variables, with a structural break in 2011Q2, which refers to the central bank's new minimum reserve policy. The paper advises that the central bank should comprehensively understand how technological advancement in the payment system affects money demand and how prior central bank policy may induce a structural break to maintain the optimality of future monetary policy.